FAKTOR–FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayundah, Yuyun; Nasiruddin, Nasiruddin; Dumadi, Dumadi (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to prove the influence of financial distress, profitability, profit quality, company size, and reputation of KAP (Public Accounting Firm). This type of research is a quantitative research with a type of secondary data obtained from the audited financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sample selection technique is purposive sampling based on certain criteria. The data were analyzed by descriptive statistical analysis test, classical assumption test, multiple regression analysis, and hypothesis test. The test is assisted by  SPSS software. Based on the tests that have been carried out, financial distress, profitability, and the size of KAP partially have a negative and significant effect on audit delay; The quality of profits partially does not have a significant effect on audit delays; the size of the company has a positive and significant effect on audit delays. In addition, financial distress, profitability, profit quality, company size, and KAP reputation simultaneously have a significant effect on audit delays